Sustainable Housing 2022
DOI: 10.5772/intechopen.98746
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Housing: Waste Management in Informal Settlements in Masvingo City, Zimbabwe

Abstract: Urban informality is fast becoming a permanent feature in cities not only in the global South but also in the global North, hence the need to include it in the delivery systems of the city for sustainable urbanity. However informal settlements are left out in the service delivery systems of cities and this has created spatial deprivation in the city. The exclusion of urban informality is not only a denial of their right to the city but also a denial of environmental justice to these people, which also constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, open innovation has been identified as having the potential to tackle challenges in waste management through collaboration and knowledge exchange (Guertler et al, 2022). It has been suggested that creating synergies between people in informal settlements and city authorities is essential for effective participatory waste management in such areas (Chigwenya & Simbanegavi, 2022). The integration of emerging technologies is vital for the future of waste management.…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, open innovation has been identified as having the potential to tackle challenges in waste management through collaboration and knowledge exchange (Guertler et al, 2022). It has been suggested that creating synergies between people in informal settlements and city authorities is essential for effective participatory waste management in such areas (Chigwenya & Simbanegavi, 2022). The integration of emerging technologies is vital for the future of waste management.…”
Section: Future Directionsmentioning
confidence: 99%